DNA polymerase zeta contributes to heterochromatin replication to prevent genome instability. (17th September 2021) - Ben Yamin, Barbara; Ahmed‐Seghir, Sana; Tomida, Junya; Despras, Emmanuelle; Pouvelle, Caroline; Yurchenko, Andrey; Goulas, Jordane; Corre, Raphael; Delacour, Quentin; Droin, Nathalie; Dessen, Philippe; Goidin, Didier; et al.
Abstract: The DNA polymerase zeta (Polζ) plays a critical role in bypassing DNA damage. REV3L, the catalytic subunit of Polζ, is also essential in mouse embryonic development and cell proliferation for reasons that remain incompletely understood. In this study, we reveal that REV3L protein interacts with heterochromatin components including repressive histone marks and localizes in pericentromeric regions through direct interaction with HP1 dimer. We demonstrate that Polζ/REV3L ensures progression of replication forks through difficult‐to‐replicate pericentromeric heterochromatin, thereby preventing spontaneous chromosome break formation. We also find that Rev3l ‐deficient cells are compromised in the repair of heterochromatin‐associated double‐stranded breaks, eliciting deletions in late‐replicating regions. Lack of REV3L leads to further consequences that may be ascribed to heterochromatin replication and repair‐associated functions of Polζ, with a disruption of the temporal replication program at specific loci. This is correlated with changes in epigenetic landscape and transcriptional control of developmentally regulated genes. These results reveal a new function of Polζ in preventing chromosome instability during replication of heterochromatic regions. Synopsis: Translesion synthesis DNA polymerase ζ (Polζ), with its catalytic subunit REV3L, is known to also limit DNA breaks in proliferating mammalian genomes, but specific consequences for replication and repair have remained unknown. This work demonstrates specific REV3L functions in limiting breaks and structural variations in heterochromatin. Inactivation of REV3L impairs replication fork speed at pericentromeres, disrupts replication timing near heterochromatin, and increases breaks and structural variations in heterochromatic regions. Polζ is targeted to heterochromatin via direct interaction with HP1. REV3L loss correlates with changes in the epigenetic landscape and transcriptional control of developmentally‐regulated genes. Abstract : HP1‐mediated targeting of REVL3, the catalytic subunit of translesion synthesis Polζ, influences replication fork progression and epigenetic and transcriptional landscapes of developmentally‐regulated genes.